1991
DOI: 10.1093/jee/84.3.891
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diets for Mass-Rearing Acheta domesticus (Orthoptera: Gryllidae) as a Novelty Food, and Comparison of Food Conversion Efficiency with Values Reported for Livestock

Abstract: As part of research on mass-rearing the cricket Acheta domesticus (L.) as a novelty (innovative) food, four cricket diets, two prepared in the laboratory and two commercial, were compared on the basis of cost per kilogram (wet weight) of eighth instars produced. Costs were influenced by dietary ingredients, mean cricket wet weight at time of harvest, and feed/gain tatios. For the laboratory-prepared diets, crickets grown on Patton's diet no. 16 or on NRC reference chick diet averaged 0.443 and 0.418 g at time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(131 citation statements)
references
References 5 publications
5
121
2
3
Order By: Relevance
“…There should be no potential hazards for people consuming crickets reared on cassava tops since hydrogen cyanide seems not to be accumulated or stored in blood and tissues (Simeonova and Fishbein, 2004). (Clifford and Woodring, 1990;Nakagaki and DeFoliart, 1991;Patton, 1963). Although there were considerable variations in nutrient content between the feeds tested in this study, there was no simple relationship between nutrient content and weight gain.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…There should be no potential hazards for people consuming crickets reared on cassava tops since hydrogen cyanide seems not to be accumulated or stored in blood and tissues (Simeonova and Fishbein, 2004). (Clifford and Woodring, 1990;Nakagaki and DeFoliart, 1991;Patton, 1963). Although there were considerable variations in nutrient content between the feeds tested in this study, there was no simple relationship between nutrient content and weight gain.…”
Section: Discussionmentioning
confidence: 73%
“…If there are no major differences in digestibility, mineral content or content of anti-nutritional substances between these feeds, the difference is most likely explained by the amino acid profile. Nakagaki and DeFoliart (1991) also found that there were no differences in weight of crickets fed a 14% CP diet (commercial non-breeding rabbit feed, 20% crude fibre) for 21 days compared with crickets fed a 22% CP diet (corn and soybean-meal based chicken diet, <5% crude fibre). Moreover, Megido et al (2016) found no correlation between dietary CP content and CP content of T. testaceus.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…One of the main reasons why insects are considered as potentially sustainable sources of animal protein is because of their high feed conversion efficiency (Nakagaki and deFoliart 1991;Berenbaum 1995;Gullan and Cranston 2005;RamosElorduy 2008;Premalatha et al 2011;Looy et al 2013). The reason for this expectation is that insects are poikilothermic.…”
Section: Feed Conversion Efficiencymentioning
confidence: 99%
“…When these figures are adjusted for edible weight (usually the entire animal cannot be eaten), the advantage of eating insects becomes even greater than other animal (Van Huis, 2013). Nakagaki and De Foliart, 1991 estimated that up to 80 percent of a cricket is edible and digestible compared with 55 percent for chicken and pigs and 40 percent for cattle.…”
Section: Benefits Of Rearing Insect For Food and Feedmentioning
confidence: 99%